2019
DOI: 10.1111/jdi.13057
|View full text |Cite
|
Sign up to set email alerts
|

Variants in the BACH2 and CLEC16A gene might be associated with susceptibility to insulin‐triggered type 1 diabetes

Abstract: Aim/IntroductionInsulin administration was found to trigger type 1 diabetes in six Japanese type 2 diabetes patients with type 1 diabetes high‐risk human leukocyte antigen class II and the class I allele of the insulin gene variable number tandem repeat genotype. The objective of the present study was to assess the contribution of non‐human leukocyte antigen single‐nucleotide polymorphisms (SNPs) to the risk of developing insulin‐triggered type 1 diabetes.Materials and MethodsWe genotyped 13 type 1 diabetes su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Type 1 diabetes is a chronic autoimmune disease that causes insulin deficiency due to immune system-mediated destruction of pancreatic β-cells. CD4 + and CD8 + T cells play an important role in the pathogenesis of this disease, and usually, autoantibodies against islet proteins can be detected [59]. Linkage and GWAS have identified more than 50 loci associated with the risk of type 1 diabetes in the human genome, and BACH2 is one of them [60].…”
Section: Type 2 Chronic Airwaymentioning
confidence: 99%
“…Type 1 diabetes is a chronic autoimmune disease that causes insulin deficiency due to immune system-mediated destruction of pancreatic β-cells. CD4 + and CD8 + T cells play an important role in the pathogenesis of this disease, and usually, autoantibodies against islet proteins can be detected [59]. Linkage and GWAS have identified more than 50 loci associated with the risk of type 1 diabetes in the human genome, and BACH2 is one of them [60].…”
Section: Type 2 Chronic Airwaymentioning
confidence: 99%
“…Finally, we tested whether converting ND β-cells to a T2D-enriched signature impairs β-cell function, as assessed by measuring intracellular Ca 2+ flux in response to glucose at the single-cell level. We selected BACH2 (due to its link to diabetes susceptibility 52 ), AFF3 (due to the strong effect on α-like-cell conversion), and TCF4 (as a negative control) for these experiments. To gate β-cells, we co-transduced ND islets with RIP-zsGreen together with adenovirus expressing each candidate TF 53 .…”
Section: Resultsmentioning
confidence: 99%
“…More is known about the function of BACH2 than that of AFF3 in islets. Traditionally viewed as a repressor of lymphocytes lineages 57 , BACH2 has been linked to genetic susceptibility to type 1 diabetes 52 , and changes to its chromatin structure have been reported in human diabetic islets 58 . In addition, it’s regulated by the Akt/mTOR pathway, has been shown to dimerize with MAF proteins 57 , and has emerged as a candidate from a previous analysis of β-cell dedifferentiation 5 , a role confirmed by the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism is still unknown, this finding supports the hypothesis that the network formed by T1DM candidate risk genes renders beta-cells hyperresponsive to danger signals. A recent study found that a BACH2 risk allele (rs3757247) might contribute to the development of insulin-triggered T1DM by affecting the immune response (81). The finding that the BACH2 gene functions at both the immune system and beta-cell levels suggests interplay between these two systems and implies an intricate network underlying T1DM pathogenesis.…”
Section: Bach2mentioning
confidence: 99%
“…A previous study found that pancreas-specific CLEC16A deficiency led to impaired glucose tolerance, ER stress and GSIS in mice, and a SNP in the CLEC16A gene (rs12708716) associated with reduced expression resulted in impaired beta-cell function in humans (98). A recent finding indicated that risk variants within CLEC16A might lead to insulin-triggered T1DM due to less efficient negative selection in the thymus (81). These findings shed light on how mitophagy maintains and promotes beta-cell function and suggest the candidate gene CLEC16A as a new potential therapeutic target for T1DM.…”
Section: Clec16amentioning
confidence: 99%